THE COMMUNICATION AND COOPETRATION IN E-LEARNING - BURGEROVA, Jana (Trends in education, 2014)
Preparation of primary education teachers at faculties of education is influenced by innovative trends related to technologies. As an alternative or supporting method using internet technologies, e-learning has become popular at universities, not excluding conditions in Slovakia. In case of its realisation, significant changes in the field of proved pedagogic approaches and rules happen. Changes regarding distance learning (DiV) with electronic support have to be formulated in a way they approach target group of the population; the system shows increase in intellectual independence and students' creativity and at the same time integrate as a new generally didactic concept. Special categories in e-learning are communication and cooperation tools, which are, in comparison with traditional education, the most absenting to teachers. The paper presents the problem of cooperation and communication regarding tools offering LMS, prepare pilot courses with focus on communication and cooperation aspects of education, prepare methodology of creation of the system courses and offer it to teachers using e-learning from and on various level. Thus oriented e-learning could benefit faculties in offering long-life learning to primary school teachers or teachers in general; its ambition is to establish MOOC in conditions of Slovak faculties of education.
Keywords: communication; cooperation; e-learning.